Simulation test and parameter optimization of fast cut back of large thermal power plant in the condition of synchronization of large-scale wind power. (November 2021) - Wen, Libin; Hu, Hong; Li, Jun; Lu, Guangling; Zhang, Yihui; Wu, Jianxu; Dou, Qian
Abstract: Fast cut back (FCB) is an important condition in power control of steam turbine generator unit, which is closely related to the flexibility, safety and stability of thermal power unit. In this paper, the traditional single reheat steam turbine model were optimized and improved by adding the key links such as medium pressure control valve and bypass, and further adding the once through boiler, bypass control system, FCB action signal, excitation system and other models. A thermal power unit model suitable for FCB large disturbance condition simulation was established. The simulation results verify the effectiveness of the model, and meet the requirements of power system electromechanical transient simulation and FCB simulation. And then, this paper improved the PSO (Particle Swarm Optimization) algorithm, and combined the advantages of each algorithm in the aspects of calculation difficulty, convergence speed, accuracy, ability to jump out of local optimum, etc., puts forward and verifies the GA-PSO (Genetic Algorithm-PSO) optimization method. Finally, considering the stability and regulation performance of the system, the GA-PSO optimization algorithm was used to obtain the optimal values of the system component parameters. The simulation results indicated that the characteristics of optimized system damping was improved, which enhanced the regulation performance and stability of the system.